Novel nomogram developed for determining suitability of metastatic castration-resistant prostate cancer patients to receive maximum benefit from radium-223 dichloride treatment—Japanese Ra-223 Therapy in Prostate Cancer using Bone Scan Index (J-RAP-BSI) Trial - Kitajima, Kazuhiro; Igeta, Masataka; Kuyama, Junpei; Kawahara, Takashi; Suga, Tsuyoshi; Otani, Tomoaki; Sugawara, Shigeyasu; Kono, Yumiko; Tamaki, Yukihisa; Seko-Nitta, Ayumi; Ishiwata, Yoshinobu; Ito, Kimiteru; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2023)
Purpose: To develop a novel nomogram for determining radium-223 dichloride (Ra-223) treatment suitability for metastatic castration-resistant prostate cancer (mCRPC) patients. Methods: This Japanese Ra-223 Therapy in Prostate Cancer using Bone Scan Index (J-RAP-BSI) Trial was a retrospective multicenter investigation enrolled 258 mCRPC patients in Japan with Ra-223 treatment between June 2016 and August 2020, with bone scintigraphy findings before treatment, clinical data, and survival outcome available. A nomogram was constructed using prognostic factors for overall survival (OS) based on a least absolute shrinkage and selection operator Cox regression model. A sub-analysis was also conducted for patients meeting European Medicines Agency (EMA) guidelines. Results: Within a median of 17.4 months after initial Ra-223 treatment, 124 patients (48.1%) died from prostate cancer. Predictive factors included (1) sum of prior treatment history (score 0, never prior novel androgen receptor-targeted agents (ARTA) therapy, never prior taxane-based chemotherapy, and ever prior bisphosphonate/denosumab treatment), (2) Eastern Cooperative Oncology Group (ECOG) performance status, (3) prostate-specific antigen doubling time (PSADT), (4) hemoglobin, (5) lactate dehydrogenase (LDH), and (6) alkaline phosphatase (ALP) levels, and (7) automated bone scan index (aBSI) value based on bone scintigraphy. The nomogram using those factors showed good discrimination, with apparent and optimism-corrected Harrell's concordance index values of 0.748 and 0.734, respectively. Time-dependent area under the curve values at 1, 2, and 3 years were 0.771, 0.818, and 0.771, respectively. In 227 patients meeting EMA recommendation, the nomogram with seven factors showed good discrimination, with apparent and optimism-corrected Harrell's concordance index values of 0.722 and 0.704, respectively. Time-dependent area under the curve values at 1, 2, and 3 years were 0.747, 0.790, and 0.759, respectively. Conclusion: This novel nomogram including aBSI to select mCRPC patients to receive Ra-223 with significantly prolonged OS possibility was found suitable for assisting therapeutic decision-making, regardless of EMA recommendation.